2016
DOI: 10.1111/1742-6723.12612
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of flexion‐extension radiography for the detection of ligamentous cervical spine injury following a normal cervical spine computed tomography

Abstract: FER does not contribute additional diagnostic accuracy for the detection of ligamentous injury to the cervical spine following a normal CT of the cervical spine. We recommend FER be removed from cervical spine clearance protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…In addition, it was difficult to observe the C7/T1 motion segment in dynamic radiography for comatose trauma patients. Oh found that flexion–extension radiography did not contribute additional diagnostic accuracy for the detection of ligamentous injury to the cervical spine following a normal CT. It was, therefore, recommended that flexion–extension radiography should be removed from cervical spine clearance protocols.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was difficult to observe the C7/T1 motion segment in dynamic radiography for comatose trauma patients. Oh found that flexion–extension radiography did not contribute additional diagnostic accuracy for the detection of ligamentous injury to the cervical spine following a normal CT. It was, therefore, recommended that flexion–extension radiography should be removed from cervical spine clearance protocols.…”
Section: Introductionmentioning
confidence: 99%
“…die Auswirkungen auf die segmentale Stabilität schwer zu beurteilen [17]. In diesen Fällen kann die geführte seitliche Durchleuchtung unter Bildwandler eine mögliche Instabilität darstellen, der zusätzliche Nutzen dieser Untersuchungstechnik wird in der Literatur allerdings sehr kritisch betrachtet [18,19,20]. Um falsch negative Befunde zu minimieren, sollte eine solche Durchleuchtung immer unter suffizienter Analgesie unter Fixierung der Schultern durch einen in dieser Untersuchungstechnik versierten Arzt erfolgen.…”
Section: Diagnostikunclassified
“…2 Several studies have evaluated the use of F/E radiographs among blunt trauma patients, but few have addressed any long-term neurologic sequelae resulting from the F/E examination. [3][4][5][6][7][8][9][10][11][12][13] Therefore, this study evaluated the presence of neurologic sequelae among non-obtunded trauma patients who received F/E radiographs due to concern for a neck injury.…”
Section: Introductionmentioning
confidence: 99%